Evaluation of the accuracy of implants using 3D printed surgical guides in implant placem - Khanh, Nguyen Van; Loi, Nguyen Hong; Khoa, Nguyen Dang (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: The optimal position of the implant in 3 dimensions in space is the most important factor to ensure the long - term success of dental implants. Today, advanced technology can simulate the virtual implant position before surgery. Through 3D printing technology, it is possible to transfer the virtual implant position to the surgical field using a static surgical guide. This study aims to evaluate the accuracy of 3D printed surgical guides when performing implant when performed using 3D printed surgical guides. Methods: The study reports a series of clinical cases with 32 implants placed in the maxilla and mandible. The surgical guide is designed using Blue Sky Implant software. Postoperative CBCT data is combined with preoperative treatment plan data to evaluate deviations in implant position, angle between two implants, and vertical deviation. Results: The study showed implant misalignment when using 3D printed surgical guides: misalignment at the implant neck was 1.11 ± 0.67 mm; at the tip is 1.43 ± 1.053 mm; The angle is 3.01 ± 2.53o and the vertical is 0.71 ± 0.57 mm. The study noted that angular deviations, cervical, apical and vertical deviations were not statistically significant according to gender, parts of dental archs and implant position. Conclusion: Using a surgical guide can help the implant to be placed more accurately in all 3 dimensions in the maxilla/ mandible. The 3D printed surgical guide has high precision and can be used to support implant surgery